Practices and challenges in implementing tuberculosis program at medical colleges in Karnataka, India - D. Hiremath, Lalita; Sharma, Nidhi; D., Sudeepa; Shivaramakrishna, H. R.; Warbhe, Nandkishor; Lonimath, Ashwini; Burugina Nagaraja, Sharath (International Journal Of Community Medicine And Public Health, 2023)
Background: The study aimed to evaluate the implementation status of the National Tuberculosis Elimination Program (NTEP) at medical colleges in Karnataka, India, and identify the challenges encountered by the medical college core committee members. Methods: A cross-sectional study was conducted among 14 medical colleges in 2019-20, using a pre-tested, semi-structured questionnaire to collect data on various NTEP components. Results: The implementation status of NTEP activities was categorized as adequate, partially adequate, or inadequate. Results showed that certain activities such as TB notification, DMC infrastructure, TB-HIV coordination, and the formation of the NTEP core committee were adequately implemented. However, challenges such as work overload, lack of dedicated manpower, and salary constraints were encountered. Conclusions: Overall, the medical colleges involved in the study were actively implementing NTEP, but there is still room for improvement to fully optimize the implementation.